What drives banks' credit standards? An analysis based on a large bank-firm panel - Donata Faccia; Franziska Hünnekes; Petra Köhler-Ulbrich (European Central Bank (ECB), 2024)
In this paper we build a unique dataset to study how banks decide which firms to lend to and how this decision depends on their own situation and the characteristics of their borrowers. We find that weaker capitalised banks adjust their credit standards more than healthier banks, especially for firms with a higher default risk. We also show how credit standards change in reaction to two specific macroeconomic developments, namely an increase in bank funding costs and a sudden deterioration in banks' corporate loan portfolios. Here we find that weaker banks respond more forcefully by tightening their credit standards more than better capitalised banks. This development is particularly pronounced when banks are linked to riskier firms. Insofar, we provide evidence of heterogeneity in the bank lending channel, depending on the situation of the lenders and the borrowers.
Keywords: E44; E51; E52; G21; 330; credit supply; bank lending channel; credit risk; monetary policy transmission